Enablers and Barriers of Tourism as a Driver of Economic and Social‐cultural Growth in Remote Queensland. Issue 2 (19th March 2019) - Summers, Jane; Cavaye, Jim; Woolcock, Geoffrey
Abstract : Regional and remote tourism in Australia is characterised by micro‐, small‐ and medium‐sized businesses, spatially dispersed and fragmented. Characteristics which present unique challenges for these communities attempting to develop tourism as a way of diversifying their economy. This study explored the views and experiences from residents and businesses in six remote local government areas in South Western Queensland to identify the barriers and enablers for remote communities to using tourism as a driver of economic and social‐cultural growth. We found a lack of understanding of the structure and behaviour of the tourism industry; a lack of business acumen; a lack of financial and human resources; and a reluctance to collaborate by tourism businesses to be barriers to tourism‐led economic growth. Enablers to tourism led growth included: local government support for tourism development; a sound understanding of the mechanics and structure of the tourism industry; and the capacity to engage in marketing that captured and narrated the visitor experience in digital channels.